Clinical outcome and survival of low-grade appendiceal mucinous neoplasm with different surgical treatment: A multicenter clinical retrospective study - Lu, Cunlong; Han, Zhenlong; Gao, Hui; Liu, Yongke; Li, Long; Shi, Tuo; Zhu, Houxin; Liu, Zhaoli; Cheng, Liangdong; Zhou, Yanbing (Clinical Surgical Oncology, 2025)
To explore the effects of different surgical strategies on clinical outcome and survival for the low-grade appendiceal mucinous neoplasm (LAMN), providing evidence support for the best treatment strategy. This study retrospectively analyzed the clinicopathological and survival outcome of LAMN data between 2013 and 2023 from multicenter, including preoperative, intraoperative, and postoperative data. Kaplan-Meier method and Cox regression analysis model were used for survival analysis. 184 patients pathologically diagnosed with LAMN were included. The median age was 59 (50,69) years. All the patients were performed surgery, including simple appendectomy, appendectomy with caecal resection, ileocecectomy and right hemicolectomy (RHC). Compared with extended resection, local resection achieved better short-term outcome. Appendectomy has higher OS rate compared to the RHC with pairwise comparison (97% vs. 79.2%, χ ​= ​11.14, P ​< ​0.001). Multivariate Cox regression analysis showed that age>60 years (hazard radio (HR) ​= ​1.125, 95%CI: 1.051–1.205, P ​< ​0.01), tumor recurrence (HR ​= ​7.019, 95%CI 2.226–22.135, P ​< ​0.001), adjuvant chemotherapy (HR ​= ​6.486, 95%CI 1.897–22.178, P ​= ​0.003) and recurrence risk (HR ​= ​13.303, 95%CI 4.165–42.493, P ​= ​0.002) were independent risk factors for survival of LAMN. Appendectomy showed favorable short-term outcome and OS rate compared with right hemicolectomy when the tumor is not ruptured and surgical margin is negative. Tumor recurrence, age>60 years, adjuvant chemotherapy and high recurrence risk indicates poor prognosis. Large clinical trials of surgical therapy for LAMN are urgently needed.